2024
DOI: 10.3389/fimmu.2024.1341313
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing antibody levels detected early after mRNA-based vaccination do not predict by themselves subsequent breakthrough infections of SARS-CoV-2

Roberto Alonso,
Sergio Gil-Manso,
Pilar Catalán
et al.

Abstract: The development of mRNA vaccines represented a significant achievement in response to the global health crisis during the SARS-CoV-2 pandemic. Evaluating vaccine efficacy entails identifying different anti-SARS-CoV-2 antibodies, such as total antibodies against the Receptor Binding Domain (RBD) of the S-protein, or neutralizing antibodies (NAbs). This study utilized an innovative PETIA-based kit to measure NAb, and the investigation aimed to assess whether levels of anti-RBD IgG and NAb uniformly measured 30 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Similarly, Alonso et al [ 20 ], in a study of healthy vaccinated healthcare workers, concluded that neither neutralizing antibody levels nor binding antibody levels measured at 30 days post-vaccination can be used as predictors of breakthrough infection. In the main STOPCoV study, no binding antibody levels for protection were identified [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Alonso et al [ 20 ], in a study of healthy vaccinated healthcare workers, concluded that neither neutralizing antibody levels nor binding antibody levels measured at 30 days post-vaccination can be used as predictors of breakthrough infection. In the main STOPCoV study, no binding antibody levels for protection were identified [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…We, among others, have shown that binding antibody levels cannot define protection or guide the frequency of vaccine boosters [ 16 , 17 , 18 , 19 ]. Although studies have suggested that neutralizing antibodies are more predictive, no threshold values have been established, and cross protection against variant strains has had limited study [ 20 , 21 , 22 , 23 ]. The development of potent neutralizing antibodies against SARS-CoV-2 appears to increase survival from infection [ 24 ].…”
Section: Introductionmentioning
confidence: 99%